AN ANALYSIS OF WRITING MATERIAL BASED ON ENGLISH GRAMMAR IN THE STUDENT’S TEXTBOOK FOR VOCATIONAL HIGH SCHOOL - Julia Rheinta Nata; Fungky Lusiana Sinamo; Erikson Saragih (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to reveal the feasibility, quality, and characteristics of scientific literacy assessment instruments with electrolyte and non-electrolyte solutions, to measure students' scientific literacy skills in electrolyte and non-electrolyte solutions. This study uses the development model of Oriondo and Dallo-Antonio which consists of five stages, namely planning for making assessment instruments, testing instruments, determining empirical validity, determining reliability, and interpreting scores. The initial product of the assessment instrument was validated by two experts, and one chemistry teacher. This research was conducted in three state vocational schools in Lubuklinggau City with a total of 30 students as research subjects. Data collection through developed assessment instruments. The test results of the assessment instrument were analyzed using Rasch's Item Response Theory model with the help of the Winstep 3.73 program. The chemical literacy ability assessment instrument consisting of 25 essay questions was declared feasible and valid with a minimum value of 0.75 and 0.79 on the Aiken index. The results of empirical validation show that 20 items are valid in the analysis of the results of the first trial and there are 17 items as the final product. The final product of the instrument consists of three categories of difficulty, including three items in the difficult category, 12 items in the medium category, and two items in the easy category. The assessment instrument has a high reliability score, namely the Cronbach alpha value of 0.86 in the first trial; 0.92 trial II; and 0.89 in trial III. The profile of students' scientific literacy ability is generally good, in terms of context,